2020
DOI: 10.1177/0009922820908589
|View full text |Cite
|
Sign up to set email alerts
|

Integrating Social Needs Screening and Community Health Workers in Primary Care: The Community Linkage to Care Program

Abstract: Clinic-based social needs screening has been associated with increased access to social services and improved health outcomes. Using a pragmatic study design in an urban pediatric practice, we used logistic regression to identify factors associated with successful social service uptake. From December 2017 to November 2018, 4948 households were screened for social needs, and 20% self-reported at least one. Of the 287 households with unmet needs who were referred and interested in further assistance, 43% reporte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
63
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(64 citation statements)
references
References 32 publications
1
63
0
Order By: Relevance
“…Of the studies that report connection outcomes, only a few have analyzed the factors associated with a successful connection. Building on previous findings that have identified the importance of programmatic intervention characteristics, such as intervention dosage 31,32 and length of follow-up, 32 the present study contributes novel evidence about the characteristics of social needs resources associated with a successful connection. Our results align with early qualitative evidence 7,[33][34][35] that it is easier for patients to connect with resources (1) in domains where more immediate solutions are readily available, (2) embedded within a health system as opposed to external to it, and (3) for services with more direct, less complicated pathways for access.…”
Section: Discussionmentioning
confidence: 71%
“…Of the studies that report connection outcomes, only a few have analyzed the factors associated with a successful connection. Building on previous findings that have identified the importance of programmatic intervention characteristics, such as intervention dosage 31,32 and length of follow-up, 32 the present study contributes novel evidence about the characteristics of social needs resources associated with a successful connection. Our results align with early qualitative evidence 7,[33][34][35] that it is easier for patients to connect with resources (1) in domains where more immediate solutions are readily available, (2) embedded within a health system as opposed to external to it, and (3) for services with more direct, less complicated pathways for access.…”
Section: Discussionmentioning
confidence: 71%
“…Recent studies have demonstrated that patients were more likely to access an SDOH resource when they received adequate outreach, assistance, and follow-up from staff. 23 , 24 Further, evidence suggests that programs involving direct staff support—compared to “light-touch” interventions (eg, that provide information only)—may be most suitable for effectively addressing SDOH. 25…”
Section: Discussionmentioning
confidence: 99%
“…26,28,90 Majority of studies reported including academic sites (n = 40), 29,[34][35][36][37][38][39][41][42][43][44][47][48][49][50][51][52][53][54][55][56][57][58][59]62,63,65,66,71,72,75,[77][78][79][80]82,84,85,89,90 including urban sites (n = 48), 26-30,32,34-56,61-63,65-68,71,72,75,77,79-81 ,83,87-90 and including the pediatric and adolescent population (n = 40). [26][27][28][29][30][35][36]…”
Section: Characteristics Of Sources Of Evidencementioning
confidence: 99%
“…Three studies described using both selfadministered and clinician-administered screening. 55,58,70 For example, in 1 model, front desk staff provided paper 31 Safety-net urgent care clinic 27 Adults with depression 31 Community health center 30,31 Women with depression 32 Women's health clinic 32 Multi-setting 26,28 Difference-indifference/quasiexperimental Urban 34 Academic primary care clinic 34 Adults 34 Not mentioned 33 Integrated health system 33 Adults with predicted high utilization 33 Pre-post with control Urban [35][36][37] Academic primary care clinic 35- 60 Elderly Hispanic adults 57 Community health center/ federally qualified health center 40,45,46,61,68,69 Pregnant women 40 Black women 49,50 Women with depression 71 Academic-federally qualified health center 39,57,62,66 Multiple populations 45,55 Unspecified primary care clinic 64,67 Not mentioned 41,60,63 Multi-primary care setting 49,50,55,58 Quality improvem...…”
Section: Screening and Responding To Unmet Needsmentioning
confidence: 99%
See 1 more Smart Citation